Should all dialysis patients with hepatitis C be treated? If so, before or after kidney transplantation?. Issue 5 (7th August 2017) - Jadoul, Michel; Martin, Paul
Abstract: HCV infection by genotype 1 and 4 can now be cured in close to 100% of patients with stage 4 or 5 CKD, including dialysis patients. Several regimens are available, all interferon‐free and given for only 12 weeks. Thus unless life expectancy is short, HCV infection should be treated. The optimal timing of antiviral treatment will be dependent on several parameters: the possibility of being transplanted rapidly (either with a HCV+ graft or from a living donor) calls for treatment after transplantation. On the contrary, severe liver fibrosis, especially with portal hypertension calls for immediate treatment of HCV. Finally specific HCV genotype also impacts the treatment decision as genotypes 2, 3, 5 and 6 currently can be treated more easily after restoration of kidney function rather than in the presence of severe CKD, although this is anticipated to change soon once newer pangenotypic regimens are licensed.